(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new Tortricidae, lsotrias huemeri sp. n., is described; the species is close to Isotrias rectifasciana (Haworth). The differences between the two species are in the pattern of wings as in the male and female genitalia.